Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Umkm Rumah Snack Anugrah Kabupaten Tangerang - Febrianti, Zalvira; Maswarni Maswarni (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to determine the Effect of Work Motivation and Work Discipline on the Performance of Employees of UMKM Rumah Snack Anugrah Tangerang Regency. In this study using a quantitative method with an associative approach. The population is all researchers totaling 50 employees. Sampling using saturated sampling techniques. The data analysis methods used are validity test, reliability test, simple linear regression test, multiple linear regression, determination coefficient analysis, correlation coefficient analysis (r), classical assumption test, and hypothesis test t test, f test. The results of the t test show that work motivation has a calculated t value> t table (3.218> 2.012) and a significant value of 0.002 <0.05, this means that work motivation significantly influences employee performance. Work discipline has a calculated t value> t table (4.246> 2.012) and a significant value of 0.000 <0.05, this means that work discipline significantly influences employee performance. Meanwhile, the results of the F-test showed a calculated F-value of 12.095 > 3.16 (calculated F>Ftable) and a sig. 0.000 <0.05, indicating that work motivation and work discipline significantly influence employee performance. The coefficient of determination (r-square) test result was 0.340, indicating that work motivation and work discipline significantly influence employee performance by 34%. The remaining 66% is influenced by other factors not examined. Keywords: Work Motivation, Work Discipline, Employee Performance